(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Fundamental rights were enshrined in the Federal Constitution of 1988, which guaranteed equality to all under the law, in addition to safeguarding the individual’s freedom, dignity and other very personal values. The new demands of contemporary society - multifaceted - invoked the recognition of the rights of the personality, as a subjective right that invokes the custody of the essential values ​​to the human person. It is still evident in Brazil the existence of a dualist society, where social exclusion prevails and plurality and diversity are not contemplated. Women, historically confined to domestic tasks, have proportionately less participation in political positions and it is in this scenario that they are concerned with exposing violations to the rights of the personality of women, their full development, freedom and opportunities. As a methodology, the deductive approach was used, with the objective of starting from a general idea, the particular idea will be arrived at, using bibliographic research.